A Petrobrás e a indústria de petróleo no Brasil: geopolítica e estratégia nacional de desenvolvimento - Wanderley Messias da Costa (Confins)
This text examines and discusses the evolution of the petroleum industry in Brazil and the central position of Petrobras in this process. Taking geopolitics as its main approach and its interactions with international relations, the study emphasizes and explores the diverse meanings of this priceless heritage won by the country over this sixty year trajectory. First of all, it exposes Brazil's outstanding position as one of the world's territorial powers and its incomparable wealth of natural resources, where oil and gas are highlighted. At the same time, the political mobilization of the 1950s inspired by the sovereign defense of national interests that resulted in the creation of Petrobras combined with the successful decision to structure it as the creative and radiating nucleus of advanced technologies that made it the world leader in exploration and production of oil in deep and ultra deep waters and made possible national self-sufficiency. From this perspective, he also explores the impact of these achievements on Brazil's projection and international insertion in this strategic area of ​​notorious economic and geopolitical significance of the world today. Finally, he emphasizes that the country must strengthen its National Defense to defend its sovereign interests, with emphasis on the jurisdictional waters and reserves of oil and gas of the South Atlantic and that, especially in the current crisis; it is incumbent upon the Brazilians to protect the assets represented by Petrobras and its strategic productive, technological and industrial chain.